Regio-isomerism directed electrocatalysis for energy efficient zinc-air battery - Mukhopadhyay, Sanchayita; Devendrachari, Mruthyunjayachari Chattanahalli; Kanade, Sandeep C.; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Thotiyl, Musthafa Ottakam (iScience, 2022)
We have investigated the role of ligand isomerism in modulating the mechanisms and kinetics associated with charge/ discharge chemistry of an aqueous metal-air battery. The dominant electron-withdrawing inductive effect (-I effect) and the diminished electron-withdrawing resonance effect (-R effect) in the alpha-NO2 isomer noticeably diminishes the rate of oxygen reduction (ORR) and oxygen evolution reactions (OER) on the catalytic Co-center. In their beta-counterpart, the cumulative -I and -R effects noticeably enhance the OER and ORR kinetics on the same catalytic Co-center. Therefore, the regioisomerism of the -NO2 functionality amplifies the kinetics of ORR/OER without influencing their mechanistic pathways. When isomeric electrocatalysts are integrated to aid the charge chemistry of a Zn-air battery, the overpotential could be decreased by similar to 250mV with beta-NO2 isomer leading to a round-trip efficiency as high as 60%. This work contributes to the design of novel molecular platforms to target the overall round-trip efficiency of energy storage and conversion devices.

Resorcinol-Azodianiline Covalent Organic Framework Supported FeOOH Quantum Dot-Catalyzed Electrochemical Ammonia Synthesis under Ambient Conditions - Shekhar, Pragalbh; Kosugi, Kento; Singh, Himan Dev; Kushwaha, Rinku; Rase, Deepak; Matsuzaki, Takumi; Jain, Chitvan; Singh, Piyush; Singh, Yashraj; Vinod, Chathakudath Prabhakaran; Kondo, Mio; Masaoka, Shigeyuki; et al. (CHEMISTRY OF MATERIALS, 2024)
Keywords: conversion; nitrogen; Recent Progress; reduction